Implementation of Performance-Based Budgeting: A Phenomenological Study on National Land Agency - Ruli Hartanto, Miftah; ., Busaini; ., Animah (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to describe the implementation of performance-based budgeting in the Regional Office of the National Land Agency of West Nusa Tenggara Province. This research was conducted by using qualitative research approach. The focus of research in this study is the implementation of performance-based budgeting in terms of budget planning, budget realization, performance evaluation, and reporting. The data used in this study include primary data and secondary data with data collection techniques such as observation, interview, and documentation study. The data in this research is analyzed using qualitative data analysis technique of interactive model from Miles and Huberman. The validity of the data obtained through triangulation test source. The results showed that in general, budget managers in the Regional Office of the National Land Agency of West Nusa Tenggara Province have understood the meaning of Performance Based Budgeting. However, so far they have not implemented Performance Based Budgeting properly because: (a) Unset and established strategic work unit level plan (b) frequent budget revisions due to incompatibility between annual work plans and actual circumstances (c) Control and evaluation system which is still weak (d) in terms of reporting performance only to meet formalities and administration.